Dependence of Energy Intensity on Economic Growth: Panel Data Analysis of South Asian Economies - Mahmood, Tahir; Ullah, Shafqut; Mumtaz, Muhammad (International Journal of Energy Economics and Policy, 2021)
The dependence of energy intensity (energy/GDP ratio) on the economic growth is studied in details for the panel of South Asian economies. Typically, it is assumed that for the technological advanced developed economies a negative relationship between energy intensity and economic growth is valid due to declining trends of energy intensity and in developing economies positive relationship between energy intensity and economic growth is valid. However, if the trend effects are removed, the growth effects may not be energy saving in under developed world. This is the main hypothesis of this study. In order to test this hypothesis, we use de-trend energy intensity (trend effect is removed). We found positive relationship between de-trended energy intensity and economic growth for the panel of underdeveloped south Asian economies. These results suggest that the energy saving options for south Asian countries are very small. Therefore, we find the cost of converting energy into GDP high in the developing economies of south Asia Keywords: Energy intensity, economic growth, Energy savings. JEL Classifications: O4, Q00, Q4 DOI: https://doi.org/10.32479/ijeep.10726